Implementing integrated care pilot projects in hospital settings – an exploration of disruptive practices. Issue 2 (7th August 2020) - Mansfield, Elizabeth; Sandercock, Jane; Dowedoff, Penny; Martel, Sara; Marcinow, Michelle; Shulman, Richard; Parks, Sheryl; Peters, Mary-Lynn; Versloot, Judith; Kerr, Jason; Zenlea, Ian
Abstract : Purpose: In Canada, integrated care pilot projects are often implemented as a local reform strategy to improve the quality of patient care and system efficiencies. In the qualitative study reported here, the authors explored the experiences of healthcare professionals when first implementing integrated care pilot projects, bringing together physical and mental health services, in a community hospital setting. Design/methodology/approach: Engaging a qualitative descriptive study design, semi-structured interviews were conducted with 24 healthcare professionals who discussed their experiences with implementing three integrated care pilot projects one year following project launch. The thematic analysis captured early implementation issues and was informed by an institutional logics framework. Findings: Three themes highlight disruptions to established logics reported by healthcare professionals during the early implementation phase: (1) integrated care practices increased workload and impacted clinical workflows; (2) integrating mental and physical health services altered patient and healthcare provider relationships; and (3) the introduction of integrated care practices disrupted healthcare team relations. Originality/value: Study findings highlight the importance of considering existing logics in healthcare settings when planning integrated care initiatives. While integrated care pilot projects can contribute to organizational, team and individual practice changes, the priorities of healthcare stakeholders, relational work required and limited project resources can create significant implementation barriers.